Online Sources for Sea Level Rise Education and Extension: AE543/AE543, 06/2020 - Her, Young Gu; Smyth, Ashley; Qiu, Jiangxiao; Bassil, Elias; Stingl, Ulrich; Reynolds, Laura (EDIS, 2020)
The impacts of sea level rise on ecosystems and natural resources are a major concern in Florida, especially in low-lying coastal areas such as south Florida. Sea level rise can impact many aspects of Florida’s economy, including urban development, agriculture, infrastructure, and natural areas. This 16-page document introduces, evaluates, and summarizes selected available online sources and tools to educate diverse stakeholders and concerned local residents on important aspects of sea level rise. Written by Young Gu Her, Ashley Smyth, Jiangxiao Qiu, Elias Bassil, Ulrich Stingl, and Laura Reynolds, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2020.